LATE PALEOCENE TO MIDDLE EOCENE CALCAREOUS NANNOFOSSIL ASSEMBLAGES FROM PENÍNSULA MITRE, SOUTHEASTERN AUSTRAL BASIN, ARGENTINA (Ameghiniana, 2023)
On the Fueguian Atlantic coast and in the southern Andean fold and thrust belt, the Paleogene is partially represented by numerous turbiditic deposits. Between Río Bueno and Cabo Leticia in Península Mitre, the Paleocene–Eocene is represented by the Río Claro Group (Cabo Leticia, La Barca, Punta Noguera, and Cerro Ruperto formations) and the Río Bueno Formation; which together constitute a ~1050-m-thick succession. Calcareous nannofossil assemblages recovered from 95 samples were analyzed to determine their relative ages. The Cabo Leticia Formation was barren in nannofossils. The upper LB2 Member of La Barca Formation contained Rhomboaster cuspis and Fasciculithus richardii, frequent in the Paleocene/Eocene boundary (subzones NP9a/NP9b). Nannofossils recovered from Punta Noguera Formation indicate an early Eocene age (biozones NP9b–NP10), with Fasciculithus tympaniformis, Rhomboaster cuspis, and abundant Toweius spp. The Cerro Ruperto Formation provided one productive sample, with specimens of Reticulofenestra spp. and Toweius spp., which indicates an early Eocene age for the formation (biozones NP12–NP13). The Río Bueno Formation yields calcareous nannofossil assemblages characterized by Chiasmolithus eograndis, Chiasmolithus expansus, Toweius spp., and Reticulofenestra spp., which indicate a late early Eocene to middle Eocene age (biozones NP14–NP15). Although the calcareous nannofossil record is discontinuous due to preservational biases in the Río Claro Group, our data allow a better age constraint for the investigated formations and to correlate these units with other surface and subsurface units in the Austral Basin.